Social Media for Customer Relationship Management Measuring Engagement Quality as Moderating - Jha, Anand Mohan; Baral, Anuja; Shrestha, Aayusha; Bhujel, Bibek; Chapai, Chirangibi; Lamichhane, Asim; Bajracharya, Rajan Bilas (NPRC Journal of Multidisciplinary Research, 2025)
Background: The increasing use of social media has transformed customer relationship management (CRM) by enhancing engagement quality. However, the extent to which social media influences engagement quality and CRM remains underexplored. This study examines the relationships between social media usage, engagement quality, and CRM to provide insights into their interconnected dynamics. Methods: This study employs a cross-sectional research design with a descriptive and explanatory approach. Data were collected from 110 respondents in Kathmandu Valley using a convenient sampling method. Results: The demographic analysis showed that the sample consisted predominantly of males (65.5%) and students (45.5%), with a mean age of 27.84 years. Descriptive statistics revealed moderate engagement with social media (mean scores ranging from 2.85 to 3.49), engagement quality (2.72 to 3.29), and CRM (2.64 to 3.54). Correlation analysis indicated significant positive relationships between social media and engagement quality (r = 0.432, p < 0.01), social media and CRM (r = 0.409, p < 0.01), and engagement quality and CRM (r = 0.541, p < 0.01), suggesting that enhanced engagement quality mediates the impact of social media on CRM. Conclusion: The findings highlight the critical role of social media in fostering engagement quality and strengthening CRM practices. Businesses and organizations should leverage social media strategies to enhance customer interactions, ultimately improving CRM effectiveness. Future studies could explore causal relationships and sector-specific variations to provide more granular insights. Novelty: This study contributes to the existing literature by empirically demonstrating the interrelationships between social media, engagement quality, and CRM within a Nepalese context. The findings offer practical implications for businesses aiming to optimize digital engagement strategies for enhanced customer relationships.